2019
DOI: 10.1105/tpc.19.00562
|View full text |Cite
|
Sign up to set email alerts
|

A PXY-Mediated Transcriptional Network Integrates Signaling Mechanisms to Control Vascular Development in Arabidopsis

Abstract: The cambium and procambium generate the majority of biomass in vascular plants. These meristems constitute a bifacial stem cell population from which xylem and phloem are specified on opposing sides by positional signals. The PHLOEM INTERCALATED WITH XYLEM (PXY) receptor kinase promotes vascular cell division and organization. However, how these functions are specified and integrated is unknown. Here, we mapped a putative PXY-mediated transcriptional regulatory network comprising 690 transcription factor-promo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
97
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 124 publications
(118 citation statements)
references
References 98 publications
0
97
0
Order By: Relevance
“…Unlike most cytokinin-responsive genes, which are regulated in the same way in root and shoot, LBD4 is specifically upregulated in the root but not in the shoot ( Brenner and Schmülling, 2012 ). LBD4 was identified as part of a feed-forward loop in a transcriptional network analysis to identify signaling mechanisms controlling vascular development ( Smit et al, 2020 ). This network transduces the signal of TDIF, a mobile CLE peptide perceived by the PXY receptor, leading to the upregulation of several WOX genes ( Hirakawa et al, 2008 , 2010 ; Etchells et al, 2013 ; Morita et al, 2016 ; Zhang et al, 2016 ).…”
Section: Transcription Factor Genes Regulated By Cytokininmentioning
confidence: 99%
“…Unlike most cytokinin-responsive genes, which are regulated in the same way in root and shoot, LBD4 is specifically upregulated in the root but not in the shoot ( Brenner and Schmülling, 2012 ). LBD4 was identified as part of a feed-forward loop in a transcriptional network analysis to identify signaling mechanisms controlling vascular development ( Smit et al, 2020 ). This network transduces the signal of TDIF, a mobile CLE peptide perceived by the PXY receptor, leading to the upregulation of several WOX genes ( Hirakawa et al, 2008 , 2010 ; Etchells et al, 2013 ; Morita et al, 2016 ; Zhang et al, 2016 ).…”
Section: Transcription Factor Genes Regulated By Cytokininmentioning
confidence: 99%
“…The rate of proliferation by periclinal cell divisions determines the width of a vascular bundle. Periclinal cell divisions in the vascular cells are controlled by several pathways: one directed by the xylem-expressed TARGET OF MONOPTEROS 5 (TMO5)/ LONESOME HIGHWAY (LHW) dimer (De Rybel et al, 2013Ohashi-Ito et al, 2014, another regulated by the phloem-expressed PHLOEM EARLY DOFs (PEARs) (Miyashima et al, 2019) and a third depending on the activity of WUSCHEL-LIKE HOMEOBOX 4 and 14 in the cambium (WOX4/14) (Etchells et al, 2013;Fisher and Turner, 2007;Hirakawa et al, 2010;Smit et al, 2020). In concert with proliferation, cells in the vascular bundle develop a pattern of distinct sub-identities.…”
Section: Introductionmentioning
confidence: 99%
“…Signal inputs from peptide-receptor interactions are integrated with GRNs that control the cambial activity. Recently, TFs and their networks controlling vascular cambium development were identified in Arabidopsis (Zhang et al, 2019;Smit et al, 2020). Starting with cambium cell-specific transcript profiling, Zhang et al (2019) extracted more than 1,200 cambium-enriched genes from modules classified based on 23 cell type-specific datasets in the Arabidopsis root.…”
Section: Establishment and Maintenance Of Vascular Cambiummentioning
confidence: 99%
“…In this analysis, WUSCHEL-RELATED HOMEOBOX 4 (WOX4), WOX14, ANAC015, KNOTTED-1-LIKE 1/BREVIPEDICELLUS (KNAT1/BP), LOB DOMAIN-CONTAINING PROTEIN 3 (LBD3), and LBD4 were identified as positive regulators of cambial activities, and SHORT VEGETATIVE PHASE (SVP), RESPONSE TO ABA AND SALT 1 (RAS1), PETAL LOSS (PTL) and MYB87 were found as negative regulators. Smit et al (2020) identified TF-promoter interactions by means of enhanced yeast one-hybrid (eY1H) screening between 812 TFs and promoters of genes regulated by TDIF-PXY. The inferred network was composed of 312 nodes and 690 edges, and its TF nodes were overrepresented by the AP2/ERF family TFs which are involved in stress responses (Etchells et al, 2012;Taylor-Teeples et al, 2015;Tsuda and Somssich, 2015).…”
Section: Establishment and Maintenance Of Vascular Cambiummentioning
confidence: 99%